Evaluation of Spanish Language Proficiency and Resources Available in Academic Pediatric Orthopaedic Centers. Issue 6 (July 2020) - Sobel, Andrew D.; Ramirez, Jose M.; Walsh, Devin F.; Defroda, Steven F.; Cruz, Aristides I.
Abstract : Introduction: Given the rapidly increasing population of Spanish-speaking patients in the United States, medical providers must have the capability to effectively communicate both with pediatric patients and their caregivers. The purpose of this study was to query the Spanish language proficiency of pediatric orthopaedic surgeons, assess the educational resources available to Spanish-speaking patients and their families, and identify the barriers to care at academic pediatric orthopaedic centers. Methods: The Web sites of medical centers within the United States that have pediatric orthopaedic surgery fellowships recognized by the Pediatric Orthopaedic Society of North America (POSNA) were accessed. Web sites were investigated for a health library as well as the availability of interpreter services. Profiles of attending surgeons within each Pediatric Orthopaedic Department were evaluated for evidence of Spanish proficiency as well as educational qualifications. Centers were contacted by phone to determine if the resources and physicians who could converse in Spanish were different than what was readily available online and if automated instructions in Spanish or a person who could converse in Spanish were available. Results: Forty-six centers with 44 fellowship programs were identified. The profiles of 12 of 334 (3.6%) surgeons who completed pediatric orthopaedic fellowships indicated Spanish proficiency. Seventeen physicians (5.1%) were identified as proficient in Spanish after phone calls. Thirty-eight pediatric orthopaedic centers (82.6%) noted interpreter service availability online, although services varied from around-the-clock availability of live interpreters to interpreter phones. When contacted by phone, 45 of 46 centers (97.8%) confirmed the availability of any interpreter service for both inpatient and outpatient settings. Sixteen centers (34.8%) had online information on orthopaedic conditions or surgical care translated into Spanish. Twenty centers (43.5%) did not have automated phone messages in Spanish or live operators that spoke Spanish. Conclusions: There is a scarcity of surgical providers in pediatric orthopaedic centers proficient in Spanish, demonstrating a large discrepancy with the growing Hispanic population. Interpreter services are widely available, although there is variability in the services provided. Considerable barriers exist to Spanish-speaking patients who attempt to access care by phone or online.